To set up the distance formula for finding the distance between points E (-6, 1) and F (2, -5), you would use the distance formula:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
Here, for point E, \( (x_1, y_1) = (-6, 1) \) and for point F, \( (x_2, y_2) = (2, -5) \).
Substituting these values into the formula, you have:
\[ d = \sqrt{(2 - (-6))^2 + (-5 - 1)^2} \]
Simplifying that gives you:
\[ d = \sqrt{(2 + 6)^2 + (-5 - 1)^2} \]
The correct setup based on the options provided is:
\[ d = (−6−2)^2+(1−(−5))^2 = \sqrt{(−6−2)^2+(1−(−5))^2} \]
However, it seems there's a transcription error in the options provided. Based on correction, the most closely aligned would resemble the correct setup after simplifying:
\[ d = \sqrt{(2 - (-6))^2 + (-5 - 1)^2} \]
Thus, the best option is:
d = \sqrt{(2 - 6)^2 + (-5 - 1)^2}
This matches with option:
d = (2−(-6))^2+(1−(-5))^2−−−−−−−−−−−−−−−−−−−√